The student edition of MATLAB : (Prentice Hall, 1997)
MATLAB offers numeric and symbolic computation, visualization and application-specific tools, with applications across engineering, science, mathematics and technical disciplines. This text offers students access to the MATLAB technical computing environment, for use on his/her personal computer.